Between Heimat and hatred : Jews and the Right in Germany, 1871-1935 - Nielsen, Philipp ca. 20./21. Jh (Oxford University Press, 2019)
From Heimat to Hatred studies German Jews involved in ventures that were from the beginning, or became increasingly, of the Right. Jewish agricultural settlement, Jews' participation in the so-called "Defense of Germandom in the East", their place in military and veteran circles and finally right-of-center politics form the core of this book. The book investigates the inherent tension in the involvement in such ventures between sincere dedication to them and the apologetic defense against antisemitic stereotypes of rootlessness, intellectualism or cosmopolitanism.